WHAT MAKES THE SECURITIES CRIMINAL LAW SYSTEM OF THE UNITED STATES WORK? ‘ALL-EMBRACING’ ‘BLANKET’ SECURITIES CRIMES AND THE LINKED ENFORCEMENT FRAMEWORK - Tajti, Tibor (Pravni zapisi, 2021)
The article explores the key factors that make the securities criminal law of the United States (US), as one of the integral building blocks of the capital markets and securities regulatory system, efficient. This includes the role and characteristics of sectoral (blanket) all-embracing securities crimes enshrined into the federal securities statutes, their nexus with general crimes, the close cooperation of the Securities Exchange Commission (SEC) and prosecutorial offices, the applicable evidentiary standards, and the fundamental policies undergirding these laws. The rich repository of US experiences should be instructive not only to the Member States of the European Union (EU) striving to forge deeper capital markets but also to those endeavoring to accede the EU (e.g., Serbia), or to create deep capital markets for which efficient prosecution of securities crimes is inevitable.